2016
DOI: 10.1177/0960327116661022
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of vitamin C against hepatotoxicity induced by emamectin benzoate in rats

Abstract: In the present study, we aimed to assess the potential protective effect of ascorbic acid (AA) against emamectin benzoate (EMB)-induced hepatotoxicity. For this purpose, biochemical, histopathological and analytical investigations were performed. Male Wistar rats were distributed into three groups, that is, a control group, an EMB group given 10 mg EMB/kg body weight (BW) by gavage and an EMB + AA group given 10 mg EMB/kg BW and vitamin C intraperitoneally (200 mg/kg). The duration of the treatment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…The ability of cinnamon inhibited DNA damage may be due to its containing of high flavonoid and polyphenol compounds (Kumar et al, 2012). The results belong to histopathological studies with EMB treatment agreed with El-Sheikh and Galal (2015), Khaldoun et al (2017) and Abou-Zeid et al (2018), who found that emamectin administration produced pathological changes in the liver. These changes include blood vessel congestion with infiltration of lymphocytes, necrosis with hepatic parenchyma infiltration, also, dilated sinusoids.…”
Section: Comet Assaysupporting
confidence: 82%
See 2 more Smart Citations
“…The ability of cinnamon inhibited DNA damage may be due to its containing of high flavonoid and polyphenol compounds (Kumar et al, 2012). The results belong to histopathological studies with EMB treatment agreed with El-Sheikh and Galal (2015), Khaldoun et al (2017) and Abou-Zeid et al (2018), who found that emamectin administration produced pathological changes in the liver. These changes include blood vessel congestion with infiltration of lymphocytes, necrosis with hepatic parenchyma infiltration, also, dilated sinusoids.…”
Section: Comet Assaysupporting
confidence: 82%
“…This increase is sustaining the hypothesis that exposure to pesticide resulted in toxicity against biochemical liver (Hernández et al, 2013). The results diagrammatic in Figure ( 4) agreed with Khaldoun et al (2017), who reported a markedly elevation of AST and ALT levels in the plasma of EMB-treated rats. These alterations of AST and ALT activity may be due to necrotic-changes of hepatic tissue that appear in histopathological examination (Figure .…”
Section: Biochemical Analysis Findingssupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, Bashandy and AlWasel (2011) described that VC normalized ALT and AST levels in rats' liver intoxicated with carbon tetrachloride. Besides, VC reduced necrosis and restored the normal appearance and structure of damaged hepatocytes due to emamectin benzoate exposure (Khaldoun Oularbi et al, 2017).…”
Section: Discussionmentioning
confidence: 86%
“…Ascorbic acid (200 mg/kg body weight) is used as a positive control in the experiment. Its protective effects on the liver are wellknown in mice with toxic liver disease induced by drugs or by various chemicals [41][42][43][44][45][46][47][48].…”
Section: Investigation Of Chitosan Vesicles Effects In Mice With Expe...mentioning
confidence: 99%